Alternative für alle? Inklusionsspezifische Analyse der AfD und ihrer Wähler*innen - Freymuth, Nina (Diskriminierungsprozesse und Teilhabeperspektiven - Herausforderungen für die Praxis der Inklusion. Ausgewählte Master-Thesen 2018-2022 des Masterstudiengangs "Soziale Inklusion: Gesundheit und Bildung" der Evangelischen Hochschule Rheinland-Westfalen-Lippe)

Approximate Computing: Balancing Performance, Power, Reliability, and Safety - Badran, Abdalrhman; Sadeghi-Kohan, Somayeh; Reimer, Jan Dennis; Hellebrand, Sybille (28th IEEE European Test Symposium (ETS'23), May 2023)

Integrating driver behavior into last-mile delivery routing: Combining machine learning and optimization in a hybrid decision support framework - Dieter, Peter; Caron, Matthew; Schryen, Guido (European Journal of Operational Research (EJOR))

Are Women (Really) More Lenient? Gender Differences in Expert Evaluations - Frick, Bernd; Spiess Bru, Clarissa; Kaimann, Daniel

Sounds too Feminine? Brand Gender and The Impact on Professional Critics - Kaimann, Daniel; Spiess Bru, Clarissa

Essays on Choices and Behavior in Competitive Situations - Beck-Werz, Lisa

Von der Grundschule in die Sekundarstufe. Übergänge ressourcenorientiert gestalten (Hrsg. von Petra Büker) - Herding, Jana; Carle, U.

‘I Feel Well, Accepted and Competent in School’—Determinants of Self-Perceived Inclusion and Academic Self-Concept in Students with Diagnosed Behavioral, Emotional and Social Difficulties (BESD) - Zdoupas, Philippos; Laubenstein, Désirée (Social Sciences)

Approximation Algorithms for Fair Range Clustering - Hotegni, Sedjro Salomon; Mahabadi, Sepideh; Vakilian, Ali (Proceedings of the 40th International Conference on Machine Learning, Honolulu, Hawaii, USA. PMLR 202, 2023.)
Keywords: Fair range clustering

The Hermeneutics of al-Sharīf al-Murtaḍā (d. 436/1044) in the Interpretation of Akhbār al-Āḥād in his Kitāb al-Amālī - Aghaei Abrandabadi, Seyed Ali (Hadith Commentary: Continuity and Change)

We Really Need to Talk About Session Tickets: A Large-Scale Analysis of Cryptographic Dangers with TLS Session Tickets - Hebrok, Sven Niclas; Nachtigall, Simon; Maehren, Marcel; Erinola, Nurullah; Merget, Robert; Somorovsky, Juraj; Schwenk, Jörg (32nd USENIX Security Symposium)

Weisheit und moralischer Intellektualismus im Koran aus intertextueller Perspektive - Dorogova, Elizaveta (Hermeneutiken der Weisheit)

Overcoming Diffusion Limitation of Faradaic Processes: Property‐Performance Relationships of 2D Conductive Metal‐Organic Framework Cu3(HHTP)2 for Reversible Lithium‐Ion Storage - Wrogemann, Jens Matthies; Lüther, Marco Joes; Bärmann, Peer; Lounasvuori, Mailis; Javed, Ali; Tiemann, Michael; Golnak, Ronny; Xiao, Jie; Petit, Tristan; Placke, Tobias; Winter, Martin (Angewandte Chemie International Edition)
Faradaic reactions including charge transfer are often accompanied with diffusion limitation inside the bulk. Conductive two-dimensional frameworks (2D MOFs) with a fast ion transport can combine both - charge transfer and fast diffusion inside their porous structure. To study remaining diffusion limitations caused by particle morphology, different synthesis routes of Cu-2,3,6,7,10,11-hexahydroxytriphenylene (Cu3(HHTP)2), a copper-based 2D MOF, are used to obtain flake- and rod-like MOF particles. Both morphologies are systematically characterized and evaluated for redox-active Li+ ion storage. The redox mechanism is investigated by means of X-ray absorption spectroscopy, FTIR spectroscopy and in situ XRD. Both types are compared regarding kinetic properties for Li+ ion storage via cyclic voltammetry and impedance spectroscopy. A significant influence of particle morphology for 2D MOFs on kinetic aspects of electrochemical Li+ ion storage can be observed. This study opens the path for optimization of redox active porous structures to overcome diffusion limitations of Faradaic processes.
Keywords: General Chemistry; Catalysis

Control of the electron dynamics in solid-state high harmonic generation on ultrafast time scales by a polarization-skewed laser pulse - Song, Xiaohong; Yang, Shidong; Wang, Guifang; Lin, Jianpeng; Wang, Liang; Meier, Torsten; Yang, Weifeng (Optics Express)
Since high-order harmonic generation (HHG) from atoms depends sensitively on the polarization of the driving laser field, the polarization gating (PG) technique was developed and applied successfully to generate isolated attosecond pulses from atomic gases. The situation is, however, different in solid-state systems as it has been demonstrated that due to collisions with neighboring atomic cores of the crystal lattice strong HHG can be generated even by elliptically- and circularly-polarized laser fields. Here we apply PG to solid-state systems and find that the conventional PG technique is inefficient for the generation of isolated ultrashort harmonic pulse bursts. In contrast, we demonstrate that a polarization-skewed laser pulse is able to confine the harmonic emission to a time window of less than one-tenth of the laser cycle. This method provides a novel way to control HHG and to generate isolated attosecond pulses in solids.
Keywords: Atomic and Molecular Physics; and Optics

Revealing the nonadiabatic tunneling dynamics in solid-state high harmonic generation - Zuo, Ruixin; Song, Xiaohong; Ben, Shuai; Meier, Torsten; Yang, Weifeng (Physical Review Research)
Keywords: General Physics and Astronomy

Manipulation of nonautonomous nonlinear wave solutions of the generalized coupled Gross–Pitaevskii equations with spin–orbit interaction and weak Raman couplings - Belobo, D. Belobo; Meier, Torsten (Results in Physics)
Keywords: General Physics and Astronomy

Dynamics of Tradition: Islamic Law and Theology in Relation

Teaching Technologies: Continuous Interplay Between Educational and Industrial Advances - Jonas-Ahrend, Gabriela; Vernholz, Mats; Temmen, Katrin (Teacher Education in the Wake of Covid-19)
The field of teaching technologies is in constant interplay between educational and industrial advances. Since the beginning of the twenty-first century, digitalization and automatization have become increasingly important. In industrial and social life, we see similar fast-moving developments. These factors challenge education, specifically vocational education, greatly, and raise two very different, yet very much connected questions: how to prepare students for their vocational lives and how to prepare teachers to communicate the necessary competencies to their students? This chapter provides an overview of advances, challenges, and possible solutions, focusing on the three key fields of vocational education in Germany: Industry 4.0, Education 4.0, and innovative teacher education. Most importantly, however, the text examines the continuous interplay between and among these fields. The beginning of the chapter is dedicated to vocational teacher education, in accordance with industrial and educational advances. Specifying this, characteristics of Industry 4.0, as well as students' and teachers' perceptions of Industry 4.0, are discussed. This is followed by an introduction to the concept of so-called learning factories as a possible way of integrating aspects of Industry 4.0 in German vocational schools. The end of the chapter is dedicated to the required changes in educational settings today and in the future. Though Industry 4.0, Education 4.0, and innovative teacher education are each widely discussed in the current literature, the interplay of all three fields reveals a research gap. This chapter tries to close this gap and provide an important contribution to the research field.

On Welding of High-Strength Steels Using Laser Beam Welding and Resistance Spot Weld Bonding with Emphasis on Seam Leak Tightness - Schmolke, Tobias; Brunner-Schwer, Christian; Biegler, Max; Rethmeier, Michael; Meschut, Gerson (Journal of Manufacturing and Materials Processing)

Screencasting: Documenting Processuality - Eckel, Julia (Screen-Images. Screenshot, Screencast, In-Game Photography)